Teaching during times of the PandemicCase study 1st year of ELE, Abou bakr Belkaid University (Tlemcen) (مجلة إحالات, 2026)
The Pandemic disrupted the teaching-learning process in universities around the world, forcingacademic bodies to adopt new teaching models, such as virtual and distance learning. As a Spanishlanguage teacher, I found myself facing challenges, with new teaching methods to achieve theteaching-learning process. In this article, I will discuss my own experience in teaching literature at adistance.